Simulated Angiography Using a Bleomycin Mixture for Sclerotherapy of Lymphatic Malformations - Guo, Lei; Wu, Changhua; Li, Xiaoyan; Song, Dan; Sun, Jiali; Zhang, Yunkui (Frontiers in Pediatrics, 2020)
Abstract Objective: Repeat sclerotherapy of lymphatic malformations (LMs) is challenging. Accordingly, the aim of the present article is to describe a simulated angiography technique―a new method of bleomycin infusion for the treatment of LMs to achieve better outcome(s) in fewer sessions. Materials and Methods: A retrospective analysis of information housed in a prospectively collected LM database was performed. Patients with LM, revealed on imaging examination and treated using a simulated angiography technique with a bleomycin mixture, were included in the study. Visual evaluation and imaging examinations were performed to evaluate clinical improvement. Results: A total of 151 patients (82 male, 69 female; mean age, 28.29 months [range 1 month–12 years]) with LMs were included in this study. Excellent visual and radiological resolution was observed in 77% (117/151) of lesions, 17% (26/151) had significant improvement, and 8 patients exhibited a slight response. The number of procedures per patient varied from 1 to 5, and the average number of treatment sessions for LM was 1.34. Side effects included skin erythema at the injection site, local swelling, mild tenderness, and fever, which were controlled by oral antipyretics. No serious side effects were observed. Conclusions: Simulated angiography using a bleomycin mixture for sclerotherapy of LMs in children was feasible and demonstrated good effect with little trauma and less time per treatment.